Utilizing Holt’s double exponential smoothing model to explain the epidemiology of HIV in Botswana (Texas Journal of Medical Science, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Botswana from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear method (HLM). The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue to decline over the out of sample period but still remain high. Therefore, policymakers must scale up HIV case detection, increase ART coverage among people living with HIV and improve coverage of HIV prevention interventions particularly among key populations.